Eco-friendly disposal of municipal solid waste and a contribution to energy crisis in India - a case study. (26th July 2022) - Parashar, Chintak Kamalesh; Das, Partha; Samanta, Subho; Banerjee, Priyabrata; Ganguly, Amit; Roy, Shibendu Shekhar; Chatterjee, Pradip Kumar
Increasing rate of generation of municipal solid waste (MSW), complexity of disposal techniques, and air-polluting emissions are major environmental issues in developing cities. In this context, this paper describes a MSW management (MSWM) pilot plant designed and developed by the Council of Scientific and Industrial Research (CSIR) laboratory, Central Mechanical Engineering Research Institute (CMERI), wherein waste from the colony (CSIR - CMERI habitat place) is collected and then mechanically segregated so as to easily dispose it in order to generate energy from the segregated wastes by waste to energy (WTE) conversion technologies and supply this energy in different forms to the society. This MSWM pilot plant strives to judiciously help our government's Clean India mission. At the end, the impact of such eco-friendly waste disposal systems was found to be very beneficial and is believed to be a real day solution which will enhance the hope of waste management scenario in an accelerated fashion.